Overexpression of plastid lipid-associated protein in marine diatom enhances the xanthophyll synthesis and storage - Jiang, Er-Ying; Fan, Yong; Phung, Nghi-Van; Xia, Wan-Yue; Hu, Guang-Rong; Li, Fu-Li (Frontiers in Microbiology, 2023)
Plastoglobules, which are lipoprotein structures surrounded by a single hydrophobic phospholipid membrane, are subcellular organelles in plant chromoplasts and chloroplasts. They contain neutral lipids, tocopherols, quinones, chlorophyll metabolites, carotenoids and their derivatives. Proteomic studies indicated that plastoglobules are involved in carotenoid metabolism and storage. In this study, one of the plastid lipid-associated proteins (PAP), the major protein in plastoglobules, was selected and overexpressed in Phaeodactylum tricornutum. The diameter of the plastoglobules in mutants was decreased by a mean of 19.2% versus the wild-type, while the fucoxanthin level was increased by a mean of 51.2%. All mutants exhibited morphological differences from the wild-type, including a prominent increase in the transverse diameter. Moreover, the unsaturated fatty acid levels were increased in different mutants, including an 18.9–59.3% increase in eicosapentaenoic acid content. Transcriptomic analysis revealed that PAP expression and the morphological changes altered xanthophyll synthesis and storage, which affected the assembly of the fucoxanthin chlorophyll a/c-binding protein and expression of antenna proteins as well as reduced the non-photochemical quenching activity of diatom cells. Therefore, metabolic regulation at the suborganelle level can be achieved by modulating PAP expression. These findings provide a subcellular structural site and target for synthetic biology to modify pigment and lipid metabolism in microalgae chassis cells.